1989
DOI: 10.1007/bf01579291
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone with physiological female steroids for presurgical therapy of male-to-female transsexualism

Abstract: The clinical and hormonal response to 12-month therapy with the antiandrogen, spironolactone, in conjunction with near-physiologic doses of female gonadal steroids in 50 transsexual males, is presented. An unselected referred series of 61 men with the psychiatric diagnosis of transsexualism was treated; 10 subjects who had received previous gonadal surgery and 1 man with Klinefelter's syndrome were excluded. Twenty-seven conventionally treated (CT; high-dose estrogen), age 34.4 +/- 10.5 years, mean +/- SD, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 20 publications
0
59
0
4
Order By: Relevance
“…Indeed, several studies reported lowering of testoster- one with cyproterone acetate 100 g/d (5,23). A synergistic effect with estrogen on the physical and emotional changes was also observed by one group with spironolactone (11). This can be particularly helpful in patients with comorbidities that prohibit high levels of estrogen.…”
Section: Feminizing Endocrine Treatment Regimens Of M3 F Transsexual mentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, several studies reported lowering of testoster- one with cyproterone acetate 100 g/d (5,23). A synergistic effect with estrogen on the physical and emotional changes was also observed by one group with spironolactone (11). This can be particularly helpful in patients with comorbidities that prohibit high levels of estrogen.…”
Section: Feminizing Endocrine Treatment Regimens Of M3 F Transsexual mentioning
confidence: 74%
“…Addition of progesterone for M3 F transsexual people is advocated by some (8,9,11). Reasons included enhanced breast growth (9,11) or to decrease irritability and breast sensitivity (8).…”
Section: Feminizing Endocrine Treatment Regimens Of M3 F Transsexual mentioning
confidence: 98%
“…Of note, the antiandrogen spironolactone is a known antihypertensive agent. One transgender genderspecific study reported a significant reduction of systolic blood pressure when spironolactone was added to the regimen of patients who had been using high-dose estrogen therapy, with a decrease from a baseline of 127.8 mm Hg (SD 13.6) to 120.5 mm Hg after one year (p < 0.05; Prior, Vigna, & Watson, 1989). Studies in nontransgender populations indicate that spironolactone is an effective blood pressure-lowering agent, particularly in refractory hypertension (Lane, Shah, & Beevers, 2007;Ouzan, Catherine, Lincoff, Carr, & Mertes, 2002).…”
Section: Possible Increased Risk: Hypertensionmentioning
confidence: 95%
“…Antiandrogens have the effect of reducing endogenous testosterone levels or testosterone activity, and thus masculine characteristics, such as body hair. They minimize the dosage of estrogen needed to suppress testosterone, thereby reducing risks associated with high dose exogenous estrogen (Prior, Vigna, Watson, Diewold, & Robinow, 1986;Prior, Vigna & Watson, 1989). Common antiandrogens include:…”
Section: Antiandrogensmentioning
confidence: 98%
“…In the second part, cross-sex hormones were given, resulting in irreversible feminization and masculinization. In some centers, spironolactone (Prior, Vigna, & Watson, 1989) or cyproterone acetate (van Kesteren, Asscheman, Megens, & Gooren, 1997) are routinely added to estrogen treatment at the beginning of the hormonal treatment, whereas in other centers cross-sex hormonal treatment is started as a unique treatment. No randomized studies are as yet available to determine the optimal dosage of hormones or the preferred regimen for the treatment of transsexuals.…”
Section: Introductionmentioning
confidence: 99%